Zweiter Beitrag zur Systematik der Blattwespengattung Tenthredo (s. str.). (Hymenoptera, Symphyta, Tenthredininae). - Taeger, Andreas (Contributions to Entomology = Beiträge zur Entomologie, 1988)
In this contribution the Palaearctic species of the Tenthredo-scrophulariae-marginella-group are revised. Several new synonymies are recognized. A key to the species of the group is given. The question of secondary homonyms in Tenthredo is discussed and some names are removed from synonymy. Nomenclatural Acts analis André, 1881 (Allantus), syn. n. of Tenthredo ussuriensis (Mocsáry, 1909) omissoides Jakovlev, 1892 (Allantus), syn. n. of Tenthredo marginella marginella Fabricius, 1793 persa Konow, 1888 (Allantus), Lectotype now a synonym of Tenthredo excellens (Konow, 1886) reitteri Konow, 1886 (Allantus), Lectotype now a synonym of Tenthredo liturata (Mocsáry, 1886) semifasciatus Rudow, 1872 (Allantus), syn. n. of Tenthredo thompsoni (Curtis, 1839) superbus Jakovlev, 1892 (Allantus), Lectotype now a synonym of Tenthredo pamyrensis Jakovlev, 1888 melanomerus Zierngiebl, 1942 (Allantus marginellus, var.), syn. n. of Tenthredo marginella marginella Fabricius, 1793 nigroscutellatus Zirngiebl, 1942 (Allantus marginellus, var.), syn. n. of Tenthredo marginella marginella Fabricius, 1793 adjecta Enslin, 1912 (Tenthredo), syn. n. of Tenthredo ussuriensis (Mocsáry, 1909) bucharica Zhelochovcev, 1976 (Tenthredo), stat. n. hitherto Tenthredo cingulifer bucharica coreana Takeuchi, 1927 (Tenthredo), Lectotype; syn. n. of Tenthredo mongolica (Jakovlev, 1892) erasa Malaise, 1945 (Tenthredo), syn. n. of Tenthredo mongolica (Jakovlev, 1892) karakorumensis (Forsius, 1935) (Tenthredo), stat. n. hitherto Allangtus variabilis var. karakorumensis khalka Takeuchi, 1940 (Tenthredo), syn. n. of Tenthredo odynerina (Malaise, 1934) marginella Fabricius, 1793 (Tenthredo), Lectotype omissa (Förster, 1844) (Tenthredo), Lectotype described as Allantus omissus variana Benson, 1930 (Tenthredo), syn. n. of Tenthredo variabilis (Mocsáry, 1909) nigripes Takeuchi, 1927 (Tenthredo coreana, var.), syn. n. of Tenthredo mongolica (Jakovlev, 1892) virago Enslin, 1913 (Tenthredo luteocincta, var.), syn. n. of Tenthredo luteocincta Eversmann, 1847 fuscipennis Konow, 1886 (Tenthredo marginella), Lectotype; stat. n. previously Allantus fuscipennis basanalis Enslin, 1912 (Tenthredo marginella, var.), Lectotype; syn. n. of Tenthredo thompsoni (Curtis, 1839) melanoceraea Enslin, 1912 (Tenthredo marginella, var.), syn. n. of Tenthredo omissa (Förster, 1844) melanomeros Enslin, 1912 (Tenthredo marginella, var.), Lectotype; syn. n. of Tenthredo omissa (Förster, 1844) schirmeri Enslin, 1918 (Tenthredo marginella, var.), syn. n. of Tenthredo omissa (Förster, 1844)